The nystagmus-associated FRMD7 gene regulates neuronal outgrowth and development - Joanne Betts‐Henderson; Stefano Bartesaghi; Moira Crosier; Susan Lindsay; Hailan Chen; Paolo Salomoni; Irène Gottlob; Pierluigi Nicotera (2009)
Mutations in the gene encoding FERM domain-containing 7 protein (FRMD7) are recognized as an important cause of X-linked idiopathic infantile nystagmus (IIN). However, the precise role of FRMD7 and its involvement in the pathogenesis of IIN are not understood. In the present study, we have explored the role of FRMD7 in neuronal development. Using in situ hybridization and immunohistochemistry, we reveal that FRMD7 expression is spatially and temporally regulated in both the human and mouse brain during embryonic and fetal development. Furthermore, we show that FRMD7 expression is up-regulated upon retinoic acid (RA)-induced differentiation of mouse neuroblastoma NEURO2A cells, suggesting FRMD7 may play a role in this process. Indeed, we demonstrate, for the first time, that knockdown of FRMD7 during neuronal differentiation results in altered neurite development. Taken together, our data suggest that FRMD7 is involved in multiple aspects of neuronal development, and have direct importance to further understanding the pathogenesis of IIN.